POTENSI ANTIJAMUR EKSTRAK METANOL AKAR MANGROVE Rhizopora apiculata TERHADAP JAMUR Candida albicans - Usman Sain; Rizal Hariyadi (PROSIDING SEMINAR KIMIA, 2018)
Mangroves generations used by the community as a medicinal ingredient. One of a breed of mangrove from plants is mangrove rhizophora apiculata. Mangrove rhizopora apiculata is a plant contained on the edge of the beach. The study is done to know compound of a metabolite secondary there are in plants mangrove rhizopora apiculata and the potential mangrove rhizopora apiculata to inhibition of the growth of fungi. Mangrove rhizopora apiculata ordinary be used as processed food .The kind of research this is research experiment. To test compound of a metabolite secondary used test qualitative. While , to inhibition of the growth of fungi used method of scratch using fungi candida albicans and aspergillus niger. Based on this research note Rhizophora apiculata mangrove leaves with methanol extract containing flavonoids, steroids, tannin, saponin. Methanol extract of roots of mangrove Rhizophora apiculata in a concentration of 1250 ppm, 2000 ppm, 5000 ppm and 10000 ppm have not been able to inhibit the growth of the fungus Candida albicans. Keywords: Root Mangrove Rhizophora apiculata, Secondary Metabolites Compounds, antifungals.